2013
DOI: 10.1089/jpm.2013.0171
|View full text |Cite
|
Sign up to set email alerts
|

Community Pharmacists' Attitudes Toward Palliative Care: An Australian Nationwide Survey

Abstract: Background: Pharmacists are among the most accessible health care professionals in the community, yet are often not involved in community palliative care teams. Objective: We investigated community pharmacists' attitudes, beliefs, feelings, and knowledge about palliative care as a first step towards determining how best to facilitate the inclusion of community pharmacists on the palliative care team. Method: A cross-sectional descriptive survey design was used. Subjects: Community pharmacists around Australia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 22 publications
(20 reference statements)
2
26
0
Order By: Relevance
“…Referral from community pharmacies or the hospital outpatient pharmacy resulted in only a small number of patients identified. This may have been due to concerns about potentially difficult conversations with patients with advanced cancer or lack of access to patient records, which has been found to be a barrier for community pharmacists talking to this patient group.…”
Section: Discussionmentioning
confidence: 99%
“…Referral from community pharmacies or the hospital outpatient pharmacy resulted in only a small number of patients identified. This may have been due to concerns about potentially difficult conversations with patients with advanced cancer or lack of access to patient records, which has been found to be a barrier for community pharmacists talking to this patient group.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with findings from a previous knowledge‐based study where nurses were found to know the most, followed by GPs and pharmacists with regard to pain assessment in palliative care (Furstenburg et al., ). Several other studies have also demonstrated a need for further pharmacist training in palliative care knowledge and issues surrounding difficult conversations (Borgsteede, Rhodius, Pasman, Onwuteaka‐Philipsen, & Rurup, ; Hussainy et al., ; O'Connor et al., ; Savage et al., ). Where pharmacists have been trained to provide community palliative care services in Scotland, healthcare professionals saw them as their “first port of call” for information about palliative medicines (Akram, Dunlop Corcoran, MacRobbie, Harrington, & Bennie, ).…”
Section: Discussionmentioning
confidence: 99%
“…tations are now carried out on a routine basis with palliative care patients in another area of West Yorkshire (Middleton-Green et al, 2016). There was a gap between the theoretical acceptability and the likelihood of actually using a medicines consultation service in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in most developing countries, palliative care is still an emerging medical specialty that require healthcare providers' contribution and participation [24][25][26][27]. In Nigeria for instance, palliative care is in its early stage of development [9,24,25,27], with services mainly limited to patients who attend the tertiary hospitals [24], while pharmacists were recognized among the least considered member of the healthcare team providing palliative care service [27][28][29][30]. In addition, the Benchmark for Minimum Academic Standard from the two major regulatory agencies for pharmacy education in Nigeria, that is the National Universities Commission and the Pharmacists Council of Nigeria does not include aspects on palliative care in the curriculum contents.…”
Section: Introductionmentioning
confidence: 99%